Consultations in general practice: a comparison of patients' and doctors' satisfaction. Issue 6706 (21st October 1989) - Rashid, A.; Forman, W.; Jagger, C.; Mann, R.
Abstract : OBJECTIVE--To provide an objective means of assessing patients' and doctors' satisfaction with a consultation. DESIGN--Questionnaire study of patients and general practitioners after consultations. SETTING--Urban general practice. SUBJECTS--250 Patients attending consecutive consultations conducted by five general practitioners. MAIN OUTCOME MEASURE--Identification of deficiencies within a consultation as perceived by both doctors and patients. RESULTS--The doctor's and patient's questionnaires for each consultation were matched and the results analysed on a group basis. The response rate for individual questions was high (81-89%). The doctors and patients significantly disagreed about the doctors' ability to assess and put patients at ease, to offer explanations and advice on treatment, and to allow expression of emotional feelings and about the overall benefit that the patients gained from the consultation. In all cases of disagreement the doctor had a more negative view of the consultation than the patient. CONCLUSIONS--The results of giving structured questionnaires on consultations to both patients and doctors could be a useful teaching tool for established doctors or those in training to improve the quality and sensitivity of care they provide.